Two Distinct Families of Protein Kinases Are Required for Plant Growth under High External Mg2+ Concentrations in Arabidopsis. Issue 3 (22nd January 2015) - Mogami, Junro; Fujita, Yasunari; Yoshida, Takuya; Tsukiori, Yoshifumi; Nakagami, Hirofumi; Nomura, Yuko; Fujiwara, Toru; Nishida, Sho; Yanagisawa, Shuichi; Ishida, Tetsuya; Takahashi, Fuminori; Morimoto, Kyoko; et al.
Abstract : Two sets of ABA-activated protein kinases and their interacting partners are required for plant growth under high external Mg 2+ concentrations in Arabidopsis. Abstract: Protein phosphorylation events play key roles in maintaining cellular ion homeostasis in higher plants, and the regulatory roles of these events in Na + and K + transport have been studied extensively. However, the regulatory mechanisms governing Mg 2+ transport and homeostasis in higher plants remain poorly understood, despite the vital roles of Mg 2+ in cellular function. A member of subclass III sucrose nonfermenting-1-related protein kinase2 (SnRK2), SRK2D/SnRK2.2, functions as a key positive regulator of abscisic acid (ABA )-mediated signaling in response to water deficit stresses in Arabidopsis ( Arabidopsis thaliana ). Here, we used immunoprecipitation coupled with liquid chromatography-tandem mass spectrometry analyses to identify Calcineurin B-like-interacting protein kinase26 (CIPK26) as a novel protein that physically interacts with SRK2D. In addition to CIPK26, three additional CIPKs (CIPK3, CIPK9, and CIPK23) can physically interact with SRK2D in planta. The srk2d/e/i triple mutant lacking all three members of subclass III SnRK2 and the cipk26/3/9/23 quadruple mutant lacking CIPK26, CIPK3, CIPK9, and CIPK23 showed reduced shoot growth under high external Mg 2+ concentrations. Similarly, several ABA biosynthesis-deficient mutants, including aba2-1, were susceptible to high external Mg 2+ concentrations. Taken together, our findings provided genetic evidence that SRK2D/E/I and CIPK26/3/9/23 are required for plant growth under high external Mg 2+ concentrations in Arabidopsis. Furthermore, we showed that ABA, a key molecule in water deficit stress signaling, also serves as a signaling molecule in plant growth under high external Mg 2+ concentrations. These results suggested that SRK2D/E/I- and CIPK26/3/9/23-mediated phosphorylation signaling pathways maintain cellular Mg 2+ homeostasis.